Orthotopic Patient-Derived Xenografts of Gastric Cancer to Decipher Drugs Effects on Cancer Stem Cells and Metastatic Dissemination - Giraud, Julie (Cancers (Basel), 2019)
Gastric cancer is the third leading cause of cancer mortality worldwide. Cancer stem cells (CSC) are at the origin of tumor initiation, chemoresistance, and the formation of metastases. However, there is a lack of mouse models enabling the study of the metastatic process in gastric adenocarcinoma (GC). The aims of this study were to develop original mouse models of patient-derived primary GC orthotopic xenografts (PDOX) allowing the development of distant metastases as preclinical models to study the anti-metastatic efficiency of drugs such as the phosphatidylinositol 3-kinase (PI3K) inhibitor Buparlisib (BKM120). Luciferase-encoding cells generated from primary GC were injected into the stomach wall of immunocompromised mice; gastric tumor and metastases development were followed by bioluminescence imaging. The anti-CSC properties of BKM120 were evaluated on the GC cells’ phenotype (CD44 expression) and tumorigenic properties in vitro and in vivo on BKM120-treated mice. After eight weeks, PDOX mice formed tumors in the stomach as well as distant metastases, that were enriched in CSC, in the liver, the lung, and the peritoneal cavity. BKM120 treatment significantly inhibited the CSC properties in vitro and reduced the number of distant metastases in mice. These new preclinical models offer the opportunity to study the anti-metastatic efficiency of new CSC-based therapeutic strategies.